2014
DOI: 10.1108/er-07-2013-0082
|View full text |Cite
|
Sign up to set email alerts
|

Configurations of e-HRM – an empirical exploration

Abstract: Purpose – The purpose of this paper is to investigate types, contexts and consequences of electronic HRM (e-HRM) configurations to get a deeper understanding of the reasons, kinds and success of different e-HRM types. Design/methodology/approach – The paper uses a cross-sectional survey of senior HR persons and analyses data with exploratory methods, i.e. cluster analysis, classification tree analysis and analysis of variance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 52 publications
2
65
1
Order By: Relevance
“…In short, existing studies have revealed a positive and significant link between e-HRM and HR service quality (Bondarouk et al, 2017;Strohmeier and Kabst, 2014;Wahyudi & Park, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In short, existing studies have revealed a positive and significant link between e-HRM and HR service quality (Bondarouk et al, 2017;Strohmeier and Kabst, 2014;Wahyudi & Park, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Remarkably, the three social e-HRM configurations are close to the eight ideal types derived from the taxonomy based on e-HRM objectives (Lepak and Snell, 1998;Strohmeier and Kabst, 2014). From this perspective, it is clear that the classification that has been widely adopted in the e-HRM literature is also of value for exploring different ways to use SM in HRM.…”
Section: Discussionmentioning
confidence: 62%
“…As in the case of the present study, this approach allows the identification of different possible configurations, each characterized by certain internal fit and alignment in terms, for example, of the HR processes supported. In this regard, while previous e-HRM studies based on configurational approach agree that operational use of IT is a precondition for a more strategic use of IT by organizations (Strohmeier and Kabst, 2014), in the case of SM, this role seems to be played by social recruitment and relational activities. Accordingly, only after having experienced the advantages deriving from the use of the SM in these areas, companies may decide to make greater use of these tools by carrying out a digitalization of transformational HR processes.…”
Section: Discussionmentioning
confidence: 86%
“…Each type of software the firm had assimilated was rated on meeting its primary objective. Like Strohmeier and Kabst (2014), answers could vary on a four-point scale (“not at all” to “totally met”). Scores were summed and divided by the number of software types to generate a portfolio score.…”
Section: Methodsmentioning
confidence: 99%
“…This finally brings us to the last set of studies – what HRTs do for the firm as a whole. Strohmeier and Kabst (2014) reported that they generally contributed to organizational success, with the impact being largest for “power users.” It should be noted, though, that their “contribution to success” construct was measured with a single-item scale lacking substantive details about what was targeted. Surveys of met expectations and results satisfaction have been similarly vague (Beckers and Bsat, 2002; Elliott and Tevavichulada, 1999; Forrer and Leibowitz, 1991; SHRM, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%